Can Pre-Treatment Assessment of Aqueous Vascular and Inflammatory Biomarkers In Patients with Macular Oedema Secondary to Retinal Vein Occlusion Guide Treatment Options? - Shankar, Jai; Hughes, Stephen Fôn; Ella-Tongwiis, Peter (Archives of Clinical and Biomedical Research, 2024)
Background: Macular oedema following Retinal Vein occlusion is the second most common cause of visual loss due to retinal vascular disease. The Royal College of Ophthalmologists recommends intra-vitreal anti- Vascular Endothelial Growth Factor (anti-VEGF) for patients with glaucoma and in young patients & steroid injections in those with recent cardiovascular events. Treatment is, both, expensive and demanding on secondary care. There is no recommendation regarding pre-treatment biomarker testing to determine which would be a better treatment option. Aims: The study aimed to determine whether vascular and inflammatory biomarkers in BRVO and CRVO differ from normal levels, and whether one can formulate an individualised treatment plan to predict whether anti-VEGF or steroids are more likely to be beneficial. Methods: Eight patients each with newly diagnosed BRVO and CRVO with macular oedema without any previous intra-vitreal injections were recruited (n=16). 100-200μl of aqueous sample was taken from the anterior chamber just prior to intra-vitreal injection of anti-VEGF agent or steroid. Aqueous samples were also collected from eight patients undergoing routine cataract surgery (n=8). ELISA was employed to assess the samples for VEGF and IL-8 levels. Results: VEGF and IL-8 levels were significantly higher in RVO as compared to controls and higher in CRVO as compared to BRVO. There were some samples with predominance of VEGF and others with IL-8. Conclusion: This study concludes that pre-treatment assessment of biomarkers may help determine whether anti-VEGF or steroid would be a better treatment option and thereby result in a significant cost reduction for the healthcare provider.